The Survival Rate and Growth of Juvenile Crayfish (Cherax quadricarinatus) With Different Types of Shelter - Jimmy Mamuaya; Winda M. Mingkid; Ockstan J. Kalesaran; Hengky J. Sinjal; Reiny A. Tumbol; John L. Tombokan (Sam Ratulangi University, 2019)
An experiment was designed to assess the relative performance of three shelter types on the survival and growth of red-claw crayfish (Cherax quadricarinatus). A 13 days old juvenile crayfish with an average length of 10 mm were cultured in 400 ml water of glass bowl and were provided with one of 3 types of shelter over 19 days. The various shelter types assessed were dried coconut leaves, bamboo and Hydrilla. Juveniles in each bowl were fed with Artemia twice a day morning and in the afternoon. There was no significant effect (P>0.05) of shelter type on the survival rate; however, there was a significant effect (P<0.05) on growth with dried coconut leaves (5.33%) performing significantly better than Hydrilla (2.33%) and bamboo (2.00%). This experiment showed that the shelter types provided had a significant effect on the growth but not in their survival.Keywords: Survival rate, Growth, juvenile Cherax quadricarinatus, ShelterABSTRAKTujuan penelitian ini adalah untuk menganalisis sintasan hidup dan pertumbuhan juvenil lobster air tawar (C. quadricarinatus) dengan shelter yang berbeda. Juvenil lobster yang berumur 13 hari dengan panjang rata rata 10 mm dipelihara dalam wadah toples kaca dengan diberikan ketiga perlakuan selama 19 hari. Ketiga jenis perlakuan adalah daun kelapa kering, bambu dan Hydrilla. Juvenil diberi pakan Artemia 2 kali sehari yaitu pada pagi dan sore hari. Hasil penelitian menunjukkan ketiga perlakuan tidak berbeda nyata terhadap sintasan hidup (P>0.05), namun berbeda nyata (P< 0.05 ) untuk pertumbuhan dengan daun kelapa kering (5.33%), Hydrilla (2.33%) dan bambu (2%). Penelitian ini menunjukkan bahwa jenis shelter memberikan pengaruh nyata terhadap pertumbuhan namun tidak berbeda nyata untuk sintasan hidup.Kata kunci: Sintasan hidup, Pertumbuhan, Juvenil Cherax quadricarinatus, Shelter